The Influence of halal awareness, lifestyle, halal literacy on halal certification interest in culinary MSMEs - Surbakti, Putri Filza Salsabila; Syahriza, Rahmi; Syakir, Ahmad (Manajemen dan Bisnis, 2025)
This study aims to analyze the influence of halal awareness, lifestyle, and halal literacy on the interest in halal certification in culinary MSMEs in Medan Johor District. The method used is a descriptive quantitative approach with a sample of 255 MSMEs. Data were collected through questionnaires and analyzed using SPSS version 25. The results showed that lifestyle and halal literacy have a positive and significant influence on the interest in halal certification, while halal awareness does not have a considerable effect. Regression tests show that lifestyle contributes 38.9% and halal literacy 38.1% to the interest in halal certification. Simultaneously, halal awareness, lifestyle, and halal literacy affect the interest in halal certification with an Adjusted R Square value of 44.3%, while other factors influence 55.7%. These findings support the Theory of Planned Behavior (TPB), where lifestyle reflects subjective norms and halal literacy increases behavioral control in the certification process. With the increasing trend of halal lifestyle, MSME actors need to adapt to market demand and increase halal literacy to support halal certification.